MANUSIA INDONESIA DALAM DIMENSI SOSIOLOGI BUDAYA - ., Moh. Muchtarom (PKn Progresif, 2015)
This article, the author wanted to explain about the human condition of Indonesia which experienced varying degrees of decadence, thus impacting the development of Indonesia's state-halting. There are two reasons why the Indonesia experience multidimensional problems, namely the existence of the nation's system of cultural values and heritage of colonization negative impact on the people of Indonesia. To overcome this problem, one solution is to use a sociological approach to the culture of the theory of Parsons and Kluckohn Talcot. Although the two are not necessarily theoretically able to answer a wide range of problems that exist in Indonesia, but at least it can be ground.